Application of the Jaya algorithm to solve the optimal reliability allocation for reduction oxygen supply system of a spacecraft - Saad Abbas Abed; Mohammad Aljanabi; Noor Hayder Abdul Ameer; Mohd Arfian Ismail; Shahreen Kasim; Rohayanti Hassan; Tole Sutikno (Institute of Advanced Engineering and Science, 2021)
In this paper the reliability of reduction oxygen supply system (ROSS) of a spacecraft which was calculated as a complex system using minimal cut method. The reliability of each component of system was calculated as well as the reliability importance of the system. The cost of each component of the system was possible approaches of the allocation values of reliability based the minimization of the overall cost in this system. The advantage of this algorithm can be used to allocate the optimization of reliability for simple or complex system. This optimization is achieved using the Jaya algorithm. The proposed technique is based on the notion that a conclusion reached on a particular problem should pass near the best results and avoid the worst outcomes. The original findings of this paper are: i) the system used in this paper is a spacecraft’s reduced oxygen supply system with the logarithmic cost function; and ii) the results obtained were by using the Jaya algorithm to solve specific system reliability optimization problems.